THE THE PROBLEMATICS OF RELIGIOSITY IN THE SANDWICH GENERATION: THE DYNAMICS OF FILIAL PIETY CONCEPT ON TWITTER AND TIKTOK SOCIAL MEDIA - Alda Ismi Azizah; Siti Khadijah; Akhmad Shodiq (Jurnal Konseling Pendidikan Islam, 2026)
This study examines the problems faced by the sandwich generation in practicing birrul walidain (devotion to parents), when religious values are confronted with complex social, economic, and psychological pressures. The sandwich generation refers to those who are simultaneously responsible for caring for elderly parents and other family members such as children or siblings, amidst financial and emotional constraints. Within this dynamic, the practice of filial devotion has undergone a shift in meaning, transforming from an act of worship into a form of compulsion. This research employs a qualitative approach with digital ethnography methods, and data were collected from Twitter and TikTok between 2019 and 2024. The findings reveal five main forms of problems: the shifting meaning of birrul walidain, financial pressure, physical and mental exhaustion, the dilemma between sincerity and compulsion, and the impact on personal life decisions. One of the root causes is the imbalance in relationships between parents and children, in which moral demands on children are very high but not accompanied by proportional parental responsibility. Several respondents voiced emotional wounds resulting from unfair or manipulative parenting patterns. On the other hand, there is a difference in moral standards: in Western contexts, filial piety is often limited to financial support, whereas in Islam, birrul walidain is comprehensive and lifelong, though it is frequently implemented without empathy for the child’s reality. Respondents do not reject the teachings of birrul walidain but seek a healthier and fairer form of practice. In the discussion, the approach of muhasabah is offered as a form of spiritual reflection, enabling the sandwich generation to fulfill their religious duties without losing inner balance. The recommendations include recontextualizing the teachings of birrul walidain, educating for healthy family relationships, and providing more empathetic social and spiritual support.